The design and development of a proposed digital management solution for the UP School of Library and Information Studies - Lowe, Frances Elaine L.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
The UP School of Library and Information Studies currently holds 1,500 theses and dissertations, photographs and newsletter, and forms. Some of the materials are difficult to access because of library or office limitations. The researcher intended to increase access and usage of these materials by developing a portal that encompasses the digitized materials. This study aimed to develop an online digital repository that shall contain four main modules for the UP SLIS materials.
The researcher followed the Systems Development Life Cycle in developing the prototype for the research. The study was divided into five development phases: the feasibility phase, the prototype designing phase, prototype development phase, prototype deployment phase, and prototype post-evaluation phase. Furthermore, in gathering important information for the development of the website, the following methods were used: pre-test surveys, feasibility interviews, prototype evaluation surveys, and task-based evaluation tests.
The pre-test surveys were used to determine the preferences and needs of the UPSLIS students, gathering a total of 57 respondents. The feasibility interviews on the other hand were used to collect opinion and insights from important individuals, the professors and the librarians. After the prototype was developed, it was evaluated by the students using an evaluation survey with 60 respondents, and a task-based evaluation test with 5 respondents.
The materials involved in the study were digitized, following the IFLA Guidelines for Digitization Projects. Data Flow Diagrams (DFDs) were used to describe the processes involved in the developed website. Code Igniter, a Model-View-Controller framework (MVC), was used to develop the website.
Results of the pre-test survey show that there was a strong need for an online digital repository from the students. Respondents mentioned that it would help them get the materials they need on their own convenience. Library hour's limitations and some students' lifestyle limit the respondents from getting their needed materials from the physical library. Lecturers also agree that it would help their students better their studies. The librarians also support the proposed project, as long as a strong security of the contents is implemented in the website.
Post-test results received positive feedback on the developed website, as rated using different categories: Navigation, Functionality, Control, Language, Feedback, Consistency, Error handling, and Visual Clarity. The task-based evaluation results also demonstrated minimal error experiences in the website.
Finally, the developed prototype entitled the UP SLIS Digital Repository was made online through a bought domain and web space from Web.Com.Ph at http://www.upslisdigitalrepository.com
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman). School of Library and Information Studies; Electronic records -- Philippines -- Quezon City; Information storage and retrieval systems